Significados que otorga el profesorado a las prácticas interculturales en un establecimiento educativo - Ibarra Bravo, Felipe (2023)
Intercultural education has become more popular in our country, Chile, over the last few years. That is why, the different educational institutions must be situated in this reality and begin to apply intercultural practices to establish an effective inclusion. Therefore, the following thesis project aims, through content analysis and a qualitative methodology, to understand what intercultural practices mean to teachers in a school located in Maipú (Santiago de Chile). This project will allow comparing and analyzing the different perceptions that exist by the teaching staff of a school in relation to this concept. Furthermore, it is expected to explore other studies regarding this topic by visualizing the phenomenon of interculturality from a new perspective. In conclusion, the relevance and contribution of this work lies in understanding the context in which the phenomenon develops, the subjective perspectives, the experiences, and the teachers' own ideas.